Plan estratégico para el desarrollo institucional del colegio de bachillerato La Maná que le permita alcanzar eficiencia y calidad en sus servicios educativos, periodo 2015-2018. - Villagomez Mendez, Luis Oswaldo (2016)
College High School located in La Maná La Maná Canton is a middle education establishment, its main objective is to forge talented young graduates; Therefore, the present thesis aims beyond the creation of a Strategic Plan that will serve as a tool for institutional development, enabling it to reach the efficiency and quality of their educational services. To carry out this investigation techniques are used as interview and surveys of teachers and administrative staff of the School of Baccalaureate Manna; methods as well as deductive, descriptive, analytical and synthetic techniques and research instruments, which together helped collect the data necessary for the development of this Strategic Plan. The development of this Strategic Plan consists of two phases, the first to establish the current situation of College High School La Maná, within which both internal and external analysis was performed, identifying strengths and weaknesses, making it easier implementation of strategies according to the real needs of the institution. In the second phase of the Strategic Plan, consisting of the strategic foundations, improvement strategies, the design of programs and projects that will support the institutional function at the development as a necessary tool to achieve efficiency and quality in its educational services it is performed. Finally the results achieved in the Strategic Plan are related to the objectives, strategies, activities, officials who contributed in preparing the Lines of Action, which contain programs and projects to be tackled, their cost and duration.